Upscaling X‐ray nanoimaging to macroscopic specimens. Issue 2 (19th February 2021) - Du, Ming; Di, Zichao (Wendy); Gürsoy, Dogˇa; Xian, R. Patrick; Kozorovitskiy, Yevgenia; Jacobsen, Chris
Abstract : In the era of diffraction‐limited storage rings, can X‐ray nanoimaging be extended to millimetre‐ or even centimetre‐sized specimens such as whole mouse brains? The authors believe so and provide size‐dependent imaging time and resource estimates based on calculated flux requirements and recent method developments in related disciplines. Abstract : Upscaling X‐ray nanoimaging to macroscopic specimens has the potential for providing insights across multiple length scales, but its feasibility has long been an open question. By combining the imaging requirements and existing proof‐of‐principle examples in large‐specimen preparation, data acquisition and reconstruction algorithms, the authors provide imaging time estimates for howX‐ray nanoimaging can be scaled to macroscopic specimens. To arrive at this estimate, a phase contrast imaging model that includes plural scattering effects is used to calculate the required exposure and corresponding radiation dose. The coherent X‐ray flux anticipated from upcoming diffraction‐limited light sources is then considered. This imaging time estimation is in particular applied to the case of the connectomes of whole mouse brains. To image the connectome of the whole mouse brain, electron microscopy connectomics might require years, whereas optimized X‐ray microscopy connectomics could reduce this to one week. Furthermore, this analysis points to challenges that need to be overcome (such as increased X‐ray detector frame rate) and opportunities that advances in artificial‐intelligence‐based `smart' scanning might provide. While the technical advances required are daunting, it is shown that X‐ray microscopy is indeed potentially applicable to nanoimaging of millimetre‐ or even centimetre‐size specimens.